An analytical study on the language policy practices and social integration of sri lanka: case study with divisional secretariat office in balangoda division - Weerasekara, W.M.N.S.; Niroshani, E. (University of Jaffna, 2012)
All human beings are born free and have equal rights without any discrimination. Language is one of the most important elements to representing the national identity. Tamils are the sufficient second major racial group in Sri Lanka. Sri Lanka is the country which has comparatively a larger public sector in Asia and public sector in Sri Lanka spreads to a wider range of sectors of the economy. After ending the civil war in Sri Lanka, although government tries to build up the national integration and finish the all discriminations between racial groups introducing regulations and programs to the administrative institutions through the ministry for national languages and social integrity, lot of Tamils are discriminated and isolated by language policy practices in Sri Lanka. Thus, examining the manipulation of the language policy in public administrative institutions & its impact to the national integration of Sri Lanka is very important. Research was selected 100 respondents covering public servants and Tamil publics using random sampling method. Questionnaires, interviews and key informant were used for quantitative and qualitative data as primary data in divisional Secretariat office in Balangoda division and secondary data was also used. Key findings of my research are (i) Tamils can't be received the public service and all documents in Tamil in administrative institutions. (ii) Government's Tamil teaching program, is unsuccessful. (iii) Public servants' Tamil language proficiency is very low. (iv) No sufficient awareness on language policy of publics. (v) Violation of language policy rights was affected to the ethnic conflict. (vi) Tamils have to receive third person's support to fill their documents and give money for them. Overly, although Sri Lankan government has implicated many language policy circulars and programs to ensure the language rights and national integrity, there is no successful manipulation of language policy in administrative institutions and it has affected to the violation the national integration of Sri Lanka.
Keywords: Human rights; Language policy; Administrative institutions; Tamils; Social integration